Penelitian Penerapan Sosial Media dalam Kegiatan Penyuluhan Pertanian pada Portal Database Garuda: Sebuah Narrative Review - Mochammad Riski Destrianto (AGRIFITIA : Journal of Agribusiness Plantation, 2023)
This study aims to find out research on the application of social media in agricultural extension activities by analysing research themes/topics, research methods, and research results. The research method uses a qualitative approach by processing data using a literature review of six references indexed by the Garuda database with publication ranges from 2014 to 2022. The results show that research on the application of social media in agricultural extension activities in Indonesia is quite good and can have a positive impact on accuracy, efficiency, and effectiveness of extension as well as increased agricultural productivity. Facebook and Twitter are social media platforms that are often used for interaction with the public, while WhatsApp is used for outreach, training and outreach activities. There is a gap between the needs and satisfaction of using WhatsApp to meet the needs of agricultural extension workers, but the relationship between the needs and satisfaction is very strong